2018
DOI: 10.1136/bmjgh-2018-000889
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of Clostridium difficile infection among hospitalised patients: results of a multicentre retrospective study in South Africa

Abstract: IntroductionLimited data exist on Clostridium difficile infection (CDI) in low-resource settings and settings with high prevalence of HIV. We aimed to determine baseline CDI patient characteristics and management and their contribution to mortality.MethodsWe reviewed adult patients hospitalised with diarrhoea and a C. difficile test result in 2015 from four public district hospitals in the Western Cape, South Africa. The primary outcome measures were risk factors for mortality. Secondary outcomes were C. diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…The long duration of TB treatment induces long-standing disruption in the gut microbiota, persisting long after the stopping of TB treatment. It was shown in South African cohorts that C. diff strains involved in CDI in patients treated for TB have high levels of resistance to rifampicin and fluoroquinolones (including moxifloxacin), a feature of the C. diff populations circulating among TB patients (21,22). In our study, we noticed a predominance of old age, a slight predominance of male subjects and urban domicile in patients with CDI.…”
Section: Discussionsupporting
confidence: 53%
“…The long duration of TB treatment induces long-standing disruption in the gut microbiota, persisting long after the stopping of TB treatment. It was shown in South African cohorts that C. diff strains involved in CDI in patients treated for TB have high levels of resistance to rifampicin and fluoroquinolones (including moxifloxacin), a feature of the C. diff populations circulating among TB patients (21,22). In our study, we noticed a predominance of old age, a slight predominance of male subjects and urban domicile in patients with CDI.…”
Section: Discussionsupporting
confidence: 53%
“…The antibiotic treatment in the pediatrics department includes ampicillin and gentamicin as the first line and third-generation cephalosporin as the second line. All children who were C. difficile positive were treated by metronidazole as recommended by South Africa treatment guidelines for CDI [26].…”
Section: Laboratorymentioning
confidence: 99%
“…Where limited data exists, a study at a tertiary hospital in Cape Town, South Africa found 22% of stool samples from patients with suspected CDI diarrhoea were C. difficile positive [2]. In addition, patients in South Africa are disproportionately affected by HIV and tuberculosis (TB) and therefore also experience known CDI risk factors of prior hospital and antibiotic exposure-exposures that can uniquely contribute to an increased risk of CDI and poor outcomes [3,4].…”
Section: Outbreaks Have Been Reported Extensively In Thementioning
confidence: 99%
“…This study reveals a more complicated process for obtaining and administering vancomycin compared to metronidazole that may be hindering healthcare providers' use of vancomycin. In an epidemiology, treatment, and outcomes study in the same setting, vancomycin was rarely ordered (2%) as initial CDI treatment [4]. One strategy is to incorporate treatment options for CDI into pharmacist education and teach pharmacists what to look for on physician-submitted motivation forms.…”
Section: Implications: Perceptions and Knowledgementioning
confidence: 99%